Analisis Pola Sebaran Lokasi Minimarket Pada Kelurahan Muara Rapak - Pratama, Hezron Ruli; Inri Pratama, Maryo; Hidayat, Arief; Putra, Rulliannor Syah (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Minmarket is part of the modern retail market, has experienced rapid growth in various residential areas, including Muara Rapak Village, Balikpapan City Minimarket has become one of the choices of the community in shopping that provides convenience and good service management to meet the daily needs of the community. These retailers offer a clean and comfortable shopping experience, longer service hours, and provide various modern payment methods. The primary aim of this research is to determine the impact of minimarket growth on the Muara Rapak Village Area. To analyze the distribution pattern, use the Average Nearest Neighbor tool. According to the observed pattern and study of minimarket distribution in Kelurahan Muara Rapak, it has a critical value (z-score) of 3.342479. Therefore, it can be concluded that the current minimarket distribution pattern is uniformly distributed. The examination of service accessibility using the buffer approach and road network assessment revealed that some minimarkets in Muara Rapak Village are unable to adequately meet the demands of the local population. Based on the results of community preferences that minimarket locations are not suitable to serve the interests of shopping, this is directly proportional to the growth of minimarkets that are uniformly patterned on one road section only.